RECONSTRUCTING TEACHER PERSPECTIVE ON CURRICULUM 2013 TOWARD OBJECTIVES AND METHOD BASED LEARNING CHARACTER OF EDUCATION - Yos Sudarman (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
As the spearhead of educational success in terms of educators, teachers, and coaches, teachers in SMP/SMA in particular, is currently faced with how to change the perspective of the curriculum and instruction, particularly for adjusting to a new setting goals and how to learn from the KSTSP to Curriculum 2013. Teaching experience in the classroom has been more oriented to knowledge and skills, slowly but surely, should be changed to materials and instructional activities that promote educational attitudes (affective), or also called character education. Concerned to education in a learning attitude in education in the curriculum in 2013 does not mean reducing the meaningfulness of competence knowledge and skills in the instruction. Indeed, the nature of the substance is humanities education as learning, which educate students moral values and attitude to the fineness of character. In other words, prioritize materials and learning activities in the sense of educating on the basic character of education, in addition to teaching the knowledge and practice the skills in learning, has become the essence of learning in Curriculum 2013, which must be followed up by the teacher with learning simple, integrated, and meaningful.